CORPUS LINGUISTICS AND THE STUDY OF ENGLISH GRAMMAR - Douglas Biber (Universitas Katolik Indonesia Atma Jaya, 2005)
This paper describes how corpus-based analyses can be employed for the study of English grammar, with a focus on case studies taken from the Longman Grammar of Spoken and Written English (LGSWE). Two major themes are developed: 1) the kinds of unexpected findings about language use that result from corpus-based investigations, and 2) the importance of register for any descriptive account of linguistic variation. Three case studies are presented: one focusing on the use of words (i.e., the most common verbs in English); the second focusing on the use and distribution of grammatical forms (i.e., the relative frequency of simple, progressive, and perfect aspect in English); and the third describing how lexis and grammatical structure can interact in complex ways (i.e., showing how verbs with the same valency patterns can have strikingly different preferences for particular valencies). In all three cases, the paper argues for the centrality of a register perspective, showing how the patterns of use vary dramatically from one register to another. Keywords: corpus-based analyses, register, linguistic variation, valency patterns